The Application of Game-Based Learning Model Improves Slow Learner Students' Learning Outcomes in Mathematics Subjects in Elementary Schools - Luluk Trihandayani; Mumpuniarti Mumpuniarti (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the application of the Game Based Learning (GBL) model in improving the learning outcomes of slow learner students in Mathematics in elementary schools. The background of this study is the low learning outcomes of Mathematics in students with special learning needs, especially slow learners, who often have difficulty understanding abstract concepts and are less motivated to learn. The GBL model was chosen because it can provide a fun, interactive learning atmosphere and motivate students to be more actively involved in the learning process. The research method used is Classroom Action Research (CAR) which is carried out in two cycles with the stages of planning, action implementation, observation, and reflection. The subjects of this study were fifth grade students of SDN 002 Kombeng who were identified as slow learners. The results of the study indicate that the application of the Game Based Learning model can improve the learning outcomes of slow learner students. This is indicated by an increase in the average value of learning outcomes in each cycle and an increase in student activity and motivation to learn. Thus, the Game Based Learning model can be an alternative effective learning strategy to help slow learner students understand Mathematics concepts in a fun and meaningful way.